Salaam Bombay! - Nair, Mira; Taraporevala, Sooni, 1957-; Syed, Shafiq; Vithal, Hansa; Sharma, Chanda; Kanwar, Aneeta; Yadav, Raghuvir; Patekar, Nana, 1951- (Eagle Home Video, 2005)
Krisha, a ten year old boy, has been abandoned in Bombay by his mother. While living in the streets, he tries to earn money to go home.